1996
DOI: 10.1136/jech.50.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Hospital volume, calendar age, and short term outcomes in patients undergoing repair of abdominal aortic aneurysms: the Ontario experience, 1988-92.

Abstract: Objective -To determine, for abdominal aortic aneurysm surgery, whether a previously reported relationship between hospital case volume and mortality rate was observed in Ontario hospitals and to assess the potential impact ofage on the mortality rate for elective surgery. Design -Population based observational study using administrative data. confidence intervals 0-88, 0.99) and 0-29 days reduction (95% CI -0-22, -0-35) in postoperative in-hospital stay. Female sex (OR 1-53, 95% CI 1-08, 2-18) and transfer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 16 publications
2
38
2
Order By: Relevance
“…In patients evaluated for the UK Small Aneurysm Trial, the rate of AAA rupture was three times higher in women than in men after adjustment for age, body size, and initial AAA diameter. 4 In several large population-based series investigators have reported the postoperative mortality rate after AAA repair to be 30% to 50% higher in women than in men, [5][6][7][8] though smaller studies have reported no difference. 9,10 There has also been recent evidence that AAA is more closely associated with stroke in women 11,12 and that women with AAA may have a higher frequency of suprarenal aortic involvement, 13,14 but these findings require confirmation.…”
Section: Methodsmentioning
confidence: 97%
“…In patients evaluated for the UK Small Aneurysm Trial, the rate of AAA rupture was three times higher in women than in men after adjustment for age, body size, and initial AAA diameter. 4 In several large population-based series investigators have reported the postoperative mortality rate after AAA repair to be 30% to 50% higher in women than in men, [5][6][7][8] though smaller studies have reported no difference. 9,10 There has also been recent evidence that AAA is more closely associated with stroke in women 11,12 and that women with AAA may have a higher frequency of suprarenal aortic involvement, 13,14 but these findings require confirmation.…”
Section: Methodsmentioning
confidence: 97%
“…Other studies have reconfirmed these observations with respect to hospital volume (341,348), surgeon experience (336), or both (349). Manheim et al (338) and Dimick et al (347) have estimated that the operative mortality rate for elective aneurysm repair is reduced by approximately 50% in high-volume hospitals in the U.S., and Wen et al (335) have calculated that there is a 6% reduction in the relative odds for death with every 10 additional elective cases that are added to the annual hospital volume in Ontario. Pearce et al (340) discovered that a doubling of the annual surgeon volume was associated with an 11% reduction in the relative risk for death after aortic aneurysm repair in Florida, and Dardik et al (339) have determined that hospital charges are significantly lower in conjunction with the repair of either intact or ruptured aortic aneurysms by high-volume surgeons in Maryland.…”
Section: Early Mortality and Complication Ratesmentioning
confidence: 97%
“…, or both(1112).Manheim et al (1091) andDimick et al (1078) have estimated that the operative mortality rate for elective aneurysm repair is reduced by approximately 50% in highvolume hospitals in the United States, and Wen et al(1088) have calculated that there is a 6% reduction in the relative odds for death with every 10 additional elective cases that are added to the annual hospital volume in Ontario, Canada. Pearce et al(1093) discovered that a doubling of the annual surgeon volume was associated with an 11% reduction in the relative risk for death after aortic aneurysm repair in Florida, and Dardik et al(1092) have determined that hospital charges are significantly lower in conjunction with the repair of either intact or ruptured aortic aneurysms by high-volume surgeons in Maryland.5.2.6.1.4.…”
mentioning
confidence: 98%